Integration of artificial immune network and K-means for cluster analysis - Kuo, R. J.; Chen, S. S.; Cheng, W. C.; Tsai, C. Y. (Knowledge and information systems, 2014)
This study is dedicated to propose a cluster analysis algorithm which is integration of artificial immune network (aiNet) and K-means algorithm (aiNetK). Four benchmark data sets, Iris, Wine, Glass, and Breast Cancer, are employed to testify the proposed algorithm. The computational results reveal that aiNetK is superior to particle swam optimization and artificial immune system-related methods.